The Twentieth Century in European Memory (Brill, 2021)
The Twentieth Century in European Memory investigates contested and divisive memories. Focusing on questions of transculturality and reception, the book looks at ways in which such memories are being shared, debated and received by museums, artists, politicians and general audiences Readership: Students and scholars of memory studies and public history, as well as students and scholars of Europan studies and contemporary European and international history, anthropology and cultural studies.